Evaluation of Extension Consultant Social Capital in Performing Extension Service to Beef Cattle Farmers in The Concentrate Production - Suarda, Andi; Dzulkifli, Andi Dzulkifli Muhammad (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
The present study aims to evaluate the social capital of livestock extension consultants in delivering extension services to farmers in beef cattle concentrate production. The study was conducted over three months in Majene and involved 25 farmers selected through random sampling techniques. Using a quantitative descriptive design, the study assessed the extent of social capital among livestock extension consultants in providing services to farmers. Two main indicators were considered: internal (discipline, trust, skill capacity) and external (cooperative network, service, communication, and regulations). Measurement instruments utilized a three-point scale: good, fair, and poor. The findings revealed that, on average, the social capital score among livestock extension consultants in delivering extension services for concentrate production was 1.55 for internal indicators and 1.47 for external indicators, classifying the social capital as fair. The skill capacity score was 2.08 (good), indicating the consultants' willingness to improve their skills. However, other indicators fell below expectations due to insufficient support, including incentives, operational costs, and transportation. Based on these findings, the social capital among extension consultants in delivering extension services can be classified as fair. Institutions must supervise extension consultants to address these challenges.